As relações entre experiência e diálogo na educação: contribuições à teoria do se-movimentar humano no horizonte da hermenêutica filosófica - Castro, Felipe Barroso de (2024)
The aim of this study is to initially understand the relationship between experience and dialog in education, in order to then point out its contributions to the Theory of Human Self-movement within the horizon of Philosophical Hermeneutics. This is a theoretical and bibliographical study in which Gadamer's hermeneutics is, at the same time, the form and content of the investigation that starts from the German philosopher's thought, considering the structure of pre-understanding and its circularity, presented in the form of a game. This, referring us to the hermeneutic experience, points to the dialogicity of education as self-formation. In order to present the notions of authentic dialog and pedagogical dialog, approximations between Gadamer's and Freire's thinking appear, especially in relation to the ethical dimension and the preconditions for dialog. As for the Theory of Human Self-movement, the presentation is based on the translated writings of Trebels and the specificities of Kunz's ideas, designed for the Brazilian reality. The fundamental points of the theory are explored in parallel with the foundations of the “Dialogical conception of movement”, where the contribution of hermeneutic experience returns, also recognizing the dimension of language and the notion of “playing and moving” with the resumption of dialogue and reference to otherness. This gives rise to problematizations and propositions such as the double aspect of assigning meanings to movement and, based on this, the notions of pre-reflexivity and reflexivity; the need for different forms of language that surround the knowledge of Physical Education and give rise to experience; and the perspective of the game, in Gadamer, as a possibility for thinking about a game of experiences and a game between experiences. Concluding the reflection provisionally, there is the possibility of establishing the relationship between “movement actor-interpreter” and “movement situation-text”, the need to recognize the experiences of failure that are associated with the instability to which the process is susceptible; the recognition of the relevance of the Theory of Self-movement to the area of Physical Education, pointing to new perspectives, as the author himself wishes; and the possibilities of hermeneutic reading as a way of understanding the theory's “sense of being”.